Analysis on 149 consecutive cases of intervertebral disc prolapse operated with microendoscopic (Metr'X) tecnique - A. Latorraca; C. Forni Niccolai Gamba (PAGEPress Publications, 2004)
Herniated disc patients represent a limited subset of patients with low back pain. Incidence of surgical intervention for lumbar disc pathology is 3% to 4%. The goal of surgery is to achieve neural decompression and relief neurological symptoms. Discectomy through laminotomy is the most common approach. More recently percutaneous approaches to lumbar discectomy, include the use of suction, laser and spinal endoscopy have evolved with mixed results. Microendoscopic discectomy (MED) combines endoscopic technology with the principles of microdiscectomy: open surgical principles are used through a tubular retractor using endoscopic visualization. We present our experience with MED in 149 patients who underwent this procedure. The patient population consisted of 83 men and 66 women aged 18 to 88 years. All patients had substantial rilief of their radiculopathy.